Neuroprotective Effect of Chlorogenic Acid on Mitochondrial Dysfunction-Mediated Apoptotic Death of DA Neurons in a Parkinsonian Mouse Model. (27th May 2020) - Singh, Saumitra Sen; Rai, Sachchida Nand; Birla, Hareram; Zahra, Walia; Rathore, Aaina Singh; Dilnashin, Hagera; Singh, Richa; Singh, Surya Pratap
Abstract : Mitochondrial dysfunction and oxidative stress characterize major factors involved in the activation of complex processes corresponding to apoptosis-mediated neuronal senescence of dopaminergic neurons (DA) in Parkinson's disease (PD). Here, we evaluated the molecular mechanisms participating in the treatment of a 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydopyridine- (MPTP-) intoxicated PD mouse model in response to chlorogenic acid (CGA). The results indicate that CGA treatment significantly improved the motor coordination of the MPTP-intoxicated mice. CGA also alleviated the fall in activity of mitochondrial complexes I, IV, and V in accordance with ameliorating the level of superoxide dismutase and mitochondrial glutathione in the midbrain of MPTP-induced mice. CGA inhibited the activation of proapoptotic proteins including Bax and caspase-3, while elevating the expression of antiapoptotic protein like Bcl-2 consequently preventing the MPTP-mediated apoptotic cascade. The study also revealed the improved phosphorylation state of Akt, ERK1/2, and GSK3 β which was downregulated as an effect of MPTP toxicity. Our findings signify that CGA may possess pharmacological properties and contribute to neuroprotection against MPTP induced toxicity in a PD mouse model associated with phosphorylation of GSK3 β via activating Akt/ERK signalling in the mitochondrial intrinsic apoptotic pathway. Thus, CGA treatment may arise as a potential therapeutic candidate for mitochondrial-mediated apoptotic senescence of DA neurons in PD.